2011
DOI: 10.1007/s10165-011-0466-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of macrophage migration inhibitory factor and their significant correlation with rheumatoid vasculitis disease activity

Abstract: Macrophage migration inhibitory factor (MIF) is recognized to be an important mediator in several inflammatory disorders, including rheumatoid arthritis (RA) and vasculitis. To evaluate the role of MIF in rheumatoid vasculitis (RV), we determined serum levels of MIF by enzyme-linked immunosorbent assay in RA patients with and without vasculitis and assessed their relationship to disease activity. Serum was obtained from 95 RA patients during active disease states [49 without vasculitis, 35 with extra-articular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Interestingly, recent studies demonstrated that coxsackievirus B3-induced myocarditis as well as human diabetes-linked LV dysfunction correlate with increased MIF concentration in the bloodstream [69], [70]. Also, high levels of MIF showed good correlation with CRP in the sera from patients with rheumatoid arthritis [71].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, recent studies demonstrated that coxsackievirus B3-induced myocarditis as well as human diabetes-linked LV dysfunction correlate with increased MIF concentration in the bloodstream [69], [70]. Also, high levels of MIF showed good correlation with CRP in the sera from patients with rheumatoid arthritis [71].…”
Section: Discussionmentioning
confidence: 98%
“…Elevated levels of MIF expression were observed in synovial tissues and synovial fluids from RA patients compared to osteoarthritis (OA) patients or healthy volunteers [ 37 ]. Specifically, the expression of MIF was closely related to the activity of RA, and its expression at higher levels indicated more severe bone erosion [ 38 ]. Functionally, MIF was required for sustaining inflammatory responses by inducing the production of proinflammatory cytokines and tissue-degrading molecules, promoting the proliferation and survival of synovial fibroblasts, stimulating the chemotaxis of neutrophils, and increasing angiogenesis and osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…RA is a rheumatic disease characterized by synovitis and systemic inflammation in which a complex network of different cytokines is known to be involved in tissue damage, but the exact mechanism of disease pathogenesis is still unknown [ 1 ]. The cytokine MIF has been associated with the inflammatory process in RA due to its important regulatory role in the immune response [ 2 ]. Regarding this, it has been described that MIF can be stimulated by the persistent proinflammatory response in RA, and that it can promote the activation of phospholipase A2 (PLA2) and the production of cyclooxygenase-2 (COX-2) and prostaglandin E2 (PGE2) in multiple immune cells that are associated with joint inflammation and the promotion of the production of proinflammatory cytokines that play a crucial role in early and established RA, such as TNF-α, interferon (IFN)-γ, IL-1β, IL-6 [ 3 ], and IL-17 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is an autoimmune chronic disease associated with high levels of proinflammatory cytokines, secreted mainly by mononuclear cells such as T lymphocytes and macrophages [ 1 ]. Macrophage migration inhibitory factor (MIF) is an inflammatory mediator that participates in the regulation of the immune response and plays an important role in the joint destruction process in RA [ 2 ]. In macrophages and synovial fibroblasts, MIF induces the expression of tissue-destructive cytokines and mediators, including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, IL-8, and some matrix metalloproteinases (MMP) such as MMP-1 and MMP-3 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%